Carbohydrate Loading Followed by High Carbohydrate Intake During Prolonged Physical Exercise and Its Impact on Glucose Control in Individuals With Diabetes Type 1—An Exploratory Study - Mattsson, Stig; Jendle, Johan; Adolfsson, Peter (Frontiers in Endocrinology, 2019)
Background Prolonged physical exercise (PE) is a challenge in type 1 diabetes with an increased incidence of both hypoglycemia and hyperglycemia. . Purpose To evaluate the impact of two consecutive days of carbohydrate (CHO) loading, followed by high intermittent CHO-intake during prolonged PE, facilitated by a proactive use of Real-Time Continuous Glucose Monitoring (rtCGM), on glucose control in individuals with type 1 diabetes. Methods Ten physically active individuals with type 1 diabetes were invited to participate in a 3-day long sports camp with the objective to evaluate CHO-loading and high intermittent CHO-intake during prolonged PE. 1.5 months later the same procedure was evaluated in relation to a 90 km cross-country skiing race (Vasaloppet). Participants were instructed to act proactively using rtCGM with predictive alerts to maintain sensor glucose values within target range, defined as 72-180 mg/dl (4-10 mmol/l). Results Mean glucose values during CHO-loading were: day 1; 140.4±45.0 mg/dl (7.8±2.5 mmol/l) and day 2; 120.6±41.4 mg/dl (6.7±2.3 mmol/l). Mean sensor glucose at start of PE was 126.0±25.2 mg/dl (7.0±1.4 mmol/l) and throughout PE 127.8±25.2 mg/dl (7.1±1.4 mmol/l). Percentage of time spent in range (TIR) respective time spent in hypoglycemia was: CHO-loading 74.7/10.4% and during PE 94.3/0.6%. Conclusions High intermittent CHO-intake during prolonged PE combined with proactive use of rtCGM is associated with good glycemic control during prolonged exercise in individuals with diabetes type 1. However, the time spent in hypoglycemia during the 2-days of CHO-loading was 10.4% and therefore a lower basal insulin rate might be suggested to reduce the time spent in hypoglycemia.